Implementación de un proceso contable en las cabinas y cyber “Ericka Paola”, para determinar su situación económica – financiera y tributaria, durante el año 2011 - García Vélez, Candida Gissela (2012)
The development of commercial enterprises generate various changes in the sector socio - economic, this is where CPAs, should meet the real needs of the organizations and institutions and especially the importance of dealing with the use of accounting records to make decisions, on the basis of this statement was made this research work in the canton Quevedo, province of Los Rios in the cabins and Cyber "Ericka Paola" located in San Camilo road to San Carlos. Accounting records were used to sort the data collected were: baseline status, general ledger, general ledger card, transcript, trial balance, profit and loss statement and balance sheet. The objectives were: • Diagnose the current accounting position and Cyber Cabins "Ericka Paola", for the establishment of control strategies. • Apply the accounting process and determine the financial statements in the cabins and Cyber "Ericka Paola" for 2011. • Analyze it financial situation and Cyber Cabins "Ericka Paola", 2011. For the respective diagnostic technique was used SWOT analysis determined the internal and outstanding strength that owns proprietary capital to produce more relevant and weakness is the high cost of technology implementation. For financial statements, the results were: The overall balance recorded a further increase in current assets available with $ 33,517.32, the highest concentration of liabilities is used by utilities to pay $ 3,210.77 in equity while the greater participation in the capital with $ 38,202.08, on the other hand the state income showed a profit of $ 16,374.94. Financial reporting rates greater participation are: Liquidity at $ 5.04, inventory turnover with 342.33 times; debt with 14.47%, and the performance cost with 64.49%. Forms for tax taxation determined as follows: The VAT is declared on a monthly sum in the period 2011 total $ 5,088.46, while the income tax was $ 4,748.97. After the results established hypothesis is accepted at the beginning of this research work. • State Income utility determines that the cabins and Cyber "Ericka Paola", in 2011